2003
DOI: 10.2337/diacare.26.2.502
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Metabolic Effects of Insulin Lispro in Type 2 Diabetic Subjects With Overt Nephropathy

Abstract: OBJECTIVE -To assess whether the insulin analog lispro may antagonize the renal effects of IGF-1, a mediator of glomerular hyperfiltration involved in the progression of diabetic and nondiabetic chronic nephropathies. RESEARCH DESIGN AND METHODS-In a randomized crossover study, we compared the renal and metabolic responses to regular or lispro insulin (0.1 units/kg body wt) administered after a euglycemic clamp and 5 and 30 min before a standard meal to 11 type 2 diabetic patients with macroalbuminuria.RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Kulozik and Hasslacher [Kulozik and Hasslacher, 2015] recently showed that low 1,5-AG levels as indicator of transient hyperglycemia are not associated with an increased prevalence of nephropathy. Ruggenenti and colleagues [Ruggenenti et al 2003] found in a study on the renal hemodynamics that postprandial hyperperfusion of the glomeruli, which is detectable under HI therapy, does not occur under treatment with insulin lispro. It is not known to what extent this effect on glomerular hemodynamics can also be found with other IA, and whether this effect has a protective influence on the course of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Kulozik and Hasslacher [Kulozik and Hasslacher, 2015] recently showed that low 1,5-AG levels as indicator of transient hyperglycemia are not associated with an increased prevalence of nephropathy. Ruggenenti and colleagues [Ruggenenti et al 2003] found in a study on the renal hemodynamics that postprandial hyperperfusion of the glomeruli, which is detectable under HI therapy, does not occur under treatment with insulin lispro. It is not known to what extent this effect on glomerular hemodynamics can also be found with other IA, and whether this effect has a protective influence on the course of nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…96,97 Interestingly, in T2DM with macroalbuminuria, the fast-acting insulin lispro blunted postprandial increase in GFR and RPF versus regular insulin, possibly due to inhibition of insulin-like growth factor-1-dependent renal vasodilation. 98 Glucagon Receptor Antagonists Hyperglucagonemia in the fasting and postprandial state contributes to elevated blood glucose and hyperfiltration in diabetes. 48,99 Interestingly, glucagon levels increase in the course of DKD.…”
Section: Insulinmentioning
confidence: 99%
“…It has been recently reported that insulin lispro, a rapid‐acting insulin analogue with structural homology with IGF‐1, prevented glomerular hyperfiltration and offset the renal effects of meal‐associated hyperglycaemia in type 2 diabetic patients with overt nephropathy (serum creatinine <2.0 mg/dl and persistent macroalbuminuria ≥200 μg/min). The mechanism of this action might be related to IGF‐1 antagonism [55].…”
Section: Effects Of Carbohydrate Metabolism Disorders On Renal Functionmentioning
confidence: 99%